Pengaruh Penyempitan Penampang Krueng Pase terhadap Kedalaman Air Normal dan Kritis - Kurniati Kurniati; Irham Irham; Fauzi A. Gani; Fazlullah Fazlullah (Portal: Jurnal Teknik Sipil, 2022)
The Krueng Pase River is one of sources of raw water used for community needs.At this time The Krueng Pase River has undergone changes incross-sectional conditions, namely The occurrence of narrowing in several places. This cross-sectional change affects the flow pattern it passes through. Narrowing of the cross-sectional flow can cause changes in the river roughness coefficient Manning and also affect normal and critical flow conditions due to changes in flow velocity and cross-sectional area.Measurement using currentmeter and buoys for determining flow rate.the result is that there is a change in the slope to become more gentle whice causes a narrowing of the cross section due to reduced speed which affects the Manning value in the area (SoSc), steepflow.